KAJIAN PEMBERIAN PUPUK UREA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SORGUM DI LAHAN RAWA LEBAK - Bambang Fredrickus Langai; Indya Dewi; Ghina Riyyani (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
The research aims to determine the effect of urea fertilizer on the growth and yield of sorghum plants in lowland swampland. The method used in this research is RAL. The factor given is urea fertilizer which consists of 4 treatment levels, namely n0 = (control), n1 = (100 urea kg per ha), n2 = (200 urea kg per ha), and n3 = (300 urea kg per ha) . The results of the research showed that the application of Urea fertilizer at a rate of 300 kg ha-1 showed growth (plant height (7-9 WAP), yield components (length of fruiting panicle bunches, number of seeds per planting, weight of seeds per planting and weight of 1000 seeds) and yield (weight of seeds per hectare ) higher than when applying urea at a rate of 200 kg per ha, 100 kg per ha and without applying urea fertilizer (0 kg per ha).